Parents' experiences of donation to their child before kidney transplantation: A qualitative study. Issue 9 (11th January 2019) - Agerskov, Hanne; Thiesson, Helle; Specht, Kirsten; D. Pedersen, Birthe
Abstract: Aim and objectives: To explore parents' experiences of donation to their child before kidney transplantation. Background: Transplantation is the treatment of choice for paediatric patients with end‐stage renal disease. Living donor kidney transplantation has shown a higher long‐term transplant survival compared to deceased donor transplantation and entails a more controllable process, with shorter waiting time. Besides complex care and treatment of their child, parents must reflect on the prospects of being a donor for their child. However, little is known about the parent donor and parent caregiver perspective. Design: A qualitative exploratory study taking a phenomenological‐hermeneutic approach. Method: The study was conducted in a Danish university hospital. Interviews were conducted with the parents of seven children, aged between 5–15 years, with end‐stage renal disease in the period before kidney transplantation. Data were analysed with inspiration from Ricoeur's theory of interpretation on three levels: naïve reading, structural analysis and critical interpretation and discussion. Results: The decision about donation was experienced as a matter of course and commitment. There were preferences for a kidney from a living donor, including the hope of being accepted as a donor. Being refused as a donor revealed feelings of powerlessness. However, transformation was performed into having a new role providing care and comfort to the child during the transplant process. Asking family and friends about donation could feel like crossing a line. Conclusion: The prospect of donating to one's child had an impact on the well‐being of the entire family. Parents were in a vulnerable situation and in need of support, regarding both living and deceased donation. Waiting time included hopeful thoughts and reflections on a new caregiver role for the child during transplantation. Relevance to clinical practice: Health professionals' attention, engagement and dialogue are essential in order to gain extensive and varied knowledge about the individual parent's experiences and the well‐being of the entire family to provide care and support before, during and after the donation and transplantation process.